A Linguistic Study of the Integration of Artificial Intelligence Tools in Teaching and Learning English Grammar - Ass.Lect Zahraa Radhi Hanoon (Journal of College of Education, 2026)
Using Artificial Intelligence (AI) in education has become very popular worldwide. It provides new and useful ways to improve teaching and help students learn better. There are big challenges to using AI in high schools in Iraq, especially for teaching English grammar. Teachers and students are often hesitant to use AI technologies, even though they have useful benefits like personalized teaching and quick feedback. This study looks at how Artificial Intelligence (AI) tools can be used in teaching English grammar. It involves 178 students from high schools and universities in Najaf, Iraq. Global trends show that AI is becoming more important in language learning, but Iraq faces special difficulties. The study showed that using AI to help teach grammar improved students' skills. However, many secondary schools were not very open to it. Surveys, classroom visits, and interviews with teachers showed that many high school teachers and students were unsure about using AI tools like grammar checkers and language-learning methods. Some teachers saw AI as a threat to traditional teaching methods, while others noticed that AI results didn't match the national curriculum. Adoption was made harder because students had trouble getting devices, having a reliable internet connection, and having a consistent power supply, especially in public schools. Even though AI has great potential for teaching, the findings show that using it successfully in Iraqi learners' secondary schools requires more than just having technology. It also needs ongoing investment in buildings and resources, training for teachers, and changes in how people think about new educational tools.
Keywords: Artificial Intelligence, Grammar, AI Tools, EFL Students, EFL Teachers